EFEKTIVITAS LITERASI SAINS PADA PEMBELAJARAN BIOLOGI - Wahdiyana; Vita; Yatin Mulyono (Jurnal Metabio, 2025)
The development of science and technology in the 21st century requires biology learning to not only focus on mastering concepts, but also on strengthening students' scientific literacy. Scientific literacy includes critical and analytical thinking skills, as well as the ability to evaluate and apply scientific information in real life. However, survey results such as PISA show that Indonesian students' scientific literacy is still relatively low, which is thought to be caused by a learning approach that is less contextual and minimally encourages active student involvement. One approach that is believed to be able to develop scientific literacy is the inquiry learning model. This study uses a meta-analysis method on eight SINTA-indexed scientific articles that examine the effectiveness of the inquiry learning model on students' critical thinking skills. The analysis was carried out by calculating the effect size value using the Cohen's d formula. The results show an average effect size value of -2.40, which statistically indicates a negative effect. However, there are extreme values ​​that significantly affect the aggregate results.